Medical identification in mass graves and its role in criminal evidence - جوني, علي مسلم; داود, صباح سامي (Journal of Legal Sciences, 2021)
Medical identification  is deemed  of  the most important evidences   in the criminal  investigation   on massive  cemeteries, as it is identified  the   unknown  individuals   either alive or died. Whereas the victims of  massive cemeteries are individuals were murdered  and then buried or  buried   alive and  thence   identifying   the bodies of the victims   should be evaluated   technically  and  need   medical experience  by checking  its   apparently or  internally (anatomically)  by  expert (Forensic  Medical Doctors)  to make the identity of victim known,  diagnosed  the  real cause of death  and its time, making  the identities of  convicts  known to prove their criminal  responsibility for  international  and national  crimes   they  made against victims. Medical Identifications   is differed  from case  to  another   according to the changes may  incur on the  buried  body, as  it  may  made by  ordinary  means or by using technologies of genetic   impression  if the bodies are pieces,  or in  advanced  stages of decay  . Thus,   medical identifications   by its results of technical or material evidences   has considerable importance   to  conclude  the fact  and  reach the justice.